Stepcut Calcaneal Lengthening Osteotomy in the Management of Stage IIB Adult-acquired Flatfoot Deformity: Surgical Technique and Review of Literature. Issue 2 (June 2020) - Metikala, Sreenivasulu; Mahmoud, Karim; Young, Kelsey; Lee, Wonyong; Wapner, Keith L.
Abstract : The treatment principles in the surgical management of stage IIB adult-acquired flatfoot deformity include rebalancing of soft-tissues, correction of deformity and preservation of subtalar joint motion. Traditional medial displacement calcaneal osteotomy addresses hindfoot valgus but has no influence on forefoot abduction. The lateral calcaneal lengthening osteotomy can achieve satisfactory improvement of forefoot abduction and uncovering of the talonavicular but cannot efficiently manage hindfoot valgus when performed in isolation. We describe stepcut calcaneal lengthening osteotomy with a "Z" design, which is essentially a combination of the above techniques with an additional full-thickness transverse cut made along the long axis of calcaneus that has the ability to obtain deformity correction of forefoot and hindfoot through a single incision. Level of Evidence: Diagnostic Level V—Expert Opinion. See Instructions for Authors for a complete description of levels of evidence.